Signals of resolve or a shortcut? Border and air space violations in the Baltic Sea region. Issue 3 (3rd July 2022) - Bussmann, Margit; Iost, Natalia
ABSTRACT: The Baltic Sea region regularly experiences low-level military incidents and violations of territorial borders. Both international media and the Baltic elite interpret Russian violations of airspace as intentional and provocative. Based on reports in the Baltic News Service on Russian airspace violations, this article assesses whether there are systematic patterns regarding geographical distribution as well as variation over time. Moreover, this article examines whether Russian airspace violations can serve as costly signals of resolve and as a deterrent to further NATO expansion.